ANALISIS FAKTOR LINGKUNGAN KELUARGA PENYEBAB ANAK TIDAK MELANJUTKAN PENDIDIKAN DI DESA BENAWAI AGUNG - Reni Yulianti; Agus Sikwan; Iwan Ramadhan (Universitas Tanjungpura, 2022)
AbstractThe purpose of this research in general is how family environmental factors cause children whoreceive free education to not continue their education in Benawai Agung Sukadana Village, NorthKayong Regency. This study uses a qualitative method with a descriptive approach. The datasources in this study were 3 parents of children who did not continue their education along with 3children who did not continue their education consisting of 1 person who did not continue to juniorhigh school and 2 people who did not continue to high school. The method used in the datacollection technique is the interview and observation method. Based on the results of the study,children did not continue their education, namely the way to educate children that was not rightand the relationship between parents and children was not harmonious. The family/homeatmosphere factor in observations and interviews was seen from the number of family membersand the number of dependents in the family, while the economic condition factor included the workof parents in terms of meeting the educational needs of children seen from the facilities providedby parents and parents' income in terms of how parents meet the educational needs of theirchildren.Keywords: Family Environment, Not Continuing Education